Pulmonary Extracellular Vesicles as Mediators of Local and Systemic Inflammation - Wahlund, Casper J. E.; Eklund, Anders; Grunewald, Johan; Gabrielsson, Susanne (Frontiers in Cell and Developmental Biology, 2017)
Cells of the airways are constantly exposed to environmental hazards including cigarette smoke, irritants, pathogens, and mechanical insults. Maintaining barrier integrity is vital, and mounting responses to threats depends on intercellular communication. Extracellular vesicles (EVs), including exosomes and microvesicles, are major signal mediators between cells, shuttling cargo in health and disease. Depending on the state of the originating cells, EVs are capable of inducing proinflammatory effects including antigen presentation, cellular migration, apoptosis induction, and inflammatory cytokine release. Cells of the airways release EVs, which can be found in bronchoalveolar lavage fluid. EVs of the airways can support inflammation in the lung, but may also exit into the circulation and carry a cocktail of pro-inflammatory molecules to recipient cells in distant organs. In this review, we discuss the possibility that EVs originating from the airways contribute to dissemination of inflammation in both lung disorders and systemic inflammatory conditions.